Collective agency: A case of common-bean smallholder farmers in Uganda - Lutomia, Cosmas Kweyu; Nchanji, Eileen; Nanyonjo, Grace; Mugagga, Isaac (2024)
Uganda is committed to addressing gender inequalities and inequities in the agricultural sector. However, systematic differences in outcomes between men and women persist. This study analyzed the role of women’s and men’s agricultural groups operating within the Mastercard Farmer Network (MFN) and non-MFN operators in influencing voice and agency among men and women farmers in 13 districts of Uganda. Descriptive analysis of data collected from 653 respondents showed that educational attainment, marital status, main occupation, household headship, mode of membership, leadership in groups, and group type all shaped the voices and agency of farmers, especially women, in these groups. The results also indicate that although MFN effectively narrowed gender differences in voice and agency, representation of women in leadership positions in groups is still low. The findings highlight the need for interventions that address the intersectionality of these factors to enhance women’s voices and agency beyond the household. Understanding the root causes and discrimination associated with women’s leadership, voice and agency needs to be understood, and solutions integrated during the formation of farmer associations, which in turn could be critical in enhancing women’s representation in group leadership.